First-Principles Study of the Effects of Ti Content on Mechanical Properties and Microscopic Mechanism in Cu2AlMn1–xTix Alloys - Kaiyang Zheng; Shuang Xu; Lisheng Liu; Jili Liu (Crystals, 2023)
It has been found that the addition of Ti can improve the strength of Cu-Al-Mn alloys and adjust their mechanical properties. However, the internal mechanism has not been fully understood. In order to clarify the influence of Ti content on the mechanical properties and microscopic mechanism of Cu-Al-Mn alloys, the mechanical, structural, and electronic properties of Cu2AlMn1–xTix (x = 0, 0.25, 0.50, 0.75, 1) alloys were studied by first-principles calculations. Results show that the substituted Ti prefers to occupy the Mn site directly due to the lower formation energy. With the increase of Ti substitution content, the L21 phase stability of the alloy improves. Moreover, the elastic modulus of the alloy increases and the anisotropy factor decreases. Further analysis shows that the proportion of antibonding states under the Fermi energy of the alloy decreases and the covalent bond is enhanced after Ti substitutes Mn, which is the main mechanism for the enhancement of stability and mechanical properties. Mulliken charges change little after Ti replaces Mn, indicating that Ti has little effect on the ionic bond strength.